Studi Kasus: Jumlah Sel Somatik dan Komposisi Susu dari Sapi Perah Positif Mastitis Subklinis Milik PT. Great Giant Livestock - Jannatun Delvia; Arifin B. Nugraha; Agik Suprayogi; Herwin Pisestyani (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2023)
An increase in the number of somatic cells to more than 400.000 cells/mL and the presence of pathogenic bacteria in the milk during normal lactation are two characteristics of subclinical mastitis. The purpose of this study was to compare subclinical mastitis-positive cows with healthy cows in terms of somatic cells count and milk composition, as well as the relationship between these two variables. Acquire from PT. Great Giant Livestock, a total of 29 fresh milk samples from 9 dairy cows tested positive for subclinical mastitis. The Breed method was used to determine the somatic cell count. Lactoscan was used to count the milk composition including fat, protein, lactose, solid non-fat, total solids, and density. The correlation between the somatic cell count and milk quality was tested using the Rank Spearman and the differences in milk quality between healthy cows and subclinical mastitis-positive cows were analyzed using Mann Whitney U. According to the data, subclinical mastitis-positive cows had more somatic cells than healthy cows. Furthermore, subclinical mastitis-affected cows provide milk of lower quality. Dairy cows with subclinical mastitis and healthy cows had significantly different milk composition (p< 0,05). The correlation between the number of somatic cells and milk composition was highly significant (p< 0,05). Subclinical mastitis-positive cows have a higher number of somatic cell and lower milk composition compared to healthy cows. The somatic cells count has a relationship with the composition of milk.